Analisis Metode Euclidean Distance dalam Menentukan Koordinat Peta pada Alamat Rumah - Kusuma, Abdi Pandu; Oktavianto, Ananda Dwi (Jurnal Teknologi dan Manajemen Informatika, 2022)
A map is drawn on a flat plane and reduced or scaled. The use of scale on a map is a comparison between the image plane and the actual surface of the earth. The earth's surface is impossible to draw according to the original, so it must be reduced by a certain ratio. The determination of the coordinates on the map is needed to determine the accuracy of the location on the home address. The coordinates which are commonly used in determining position on a map are latitude and longitude. The purpose of this study was to analyze the use of the Euclidean Distance method in mapping the coordinates of the home address. The population data taken is from the taxpayer population in Beru Village, Wlingi District. The coordinate point mapping was done using the Mapbox application. Then, the results of processing the coordinates of the map were analyzed using the Euclidean Distance method. The methods of data collection were carried out using interviews, observation, literature studies and documentation in order to obtain effective data collection.